Long-term outcomes of lateral tunneled transposed brachiobasilic arteriovenous fistulas in elderly hemodialysis patient. Issue 5 (September 2019) - Lin, Yen-Chin; Huang, Yu-Ying; Lin, Ming-Yen; Chiu, Yi-Wen; Lim, Lee-Moay; Hsieh, Chong-Chao
Background: Arteriovenous fistula is recommended for the general dialysis population, but its use remains controversial in the elderly population. We evaluated the long-term outcomes of lateral tunneled transposed brachiobasilic arteriovenous fistulas in older patients who underwent hemodialysis. Methods: In this retrospective cohort study, we included patients who received a two-stage transposed brachiobasilic arteriovenous fistula in a medical center from May 2005 to January 2014. The patients were followed up from the fistula placement date until any intervention, death, failure, January 2015, or the end of the sixth year. Death and arteriovenous fistula failure during the observation period were considered as adverse outcomes, and the cause of death was identified. The cumulative patency rate was calculated using the Kaplan–Meier approach to reveal the long-term outcomes of this procedure. Results: Among the 66 patients who underwent surgery, the average age was 65.8 ± 13.5 years and the majority were females (62.1%). After a median follow-up of 20.6 months, 19 patients died, 12 (18.2%) received vascular intervention, and 3 experienced fistula failure. No significant difference was observed in the 6-year cumulative patency rates between younger and older adults (96.3% vs 80.3%, p = 0.58). None of the deaths during the observation period were related to bloodstream infection. Conclusion: A two-stage lateral tunneled transposed brachiobasilic arteriovenous fistula can be applied to patients undergoing hemodialysis, regardless of age.